Impaired fear extinction in adolescent rodents: Behavioural and neural analyses. (November 2016) - Baker, Kathryn D.; Bisby, Madelyne A.; Richardson, Rick
Highlights: Adolescents, both rodent and human, exhibit impaired extinction retention. This deficit may be due to an imbalance in the neural circuitry of fear inhibition. Adverse environmental exposures in adolescence alter fear regulation into adulthood. Pharmacological and behavioural adjuncts augment extinction in adolescence. Fear learned before adolescence can be successfully extinguished in adolescence. Abstract: Despite adolescence being a developmental window of vulnerability, up until very recently there were surprisingly few studies on fear extinction during this period. Here we summarise the recent work in this area, focusing on the unique behavioural and neural characteristics of fear extinction in adolescent rodents, and humans where relevant. A prominent hypothesis posits that anxiety disorders peak during late childhood/adolescence due to the non-linear maturation of the fear inhibition neural circuitry. We discuss evidence that impaired extinction retention in adolescence is due to subregions of the medial prefrontal cortex and amygdala mediating fear inhibition being underactive while other subregions that mediate fear expression are overactive. We also review work on various interventions and surprising circumstances which enhance fear extinction in adolescence. This latter work revealed that the neural correlates of extinction in adolescence are different to that in younger and older animals even when extinction retention is not impaired. This growing body of work highlights that adolescence is a unique period of development for fear inhibition.